Chromium Complexes of Benzylic Cations: A Synthetic, High Field NMR Spectroscopic and EHMO Study - Downton, Patricia Ann (My University, 1991)
Treatment of chromium hexacarbonyl with a series of benzyl alcohols yields the corresponding (R-C6H4CH2OH)Cr(CO)3 complexes, where R = 3-methoxy, 3-methyl, 4-methoxy or 4-methyl. These complexes were characterized by NMR spectroscopy.
Protonation of the tricarbonylchromium alcohols with CF3SO3H at low temperature yields a benzyl cation complex which can be isolated and examined by variable-temperature 13C NMR spectroscopy. The spectra show a splitting of the carbonyl carbons at low temperature, providing evidence of electronically restricted rotation of the tripodal ligand. Evaluation of the simulated spectra provides the rotational barrier for this dynamic process. These results are rationalized by means of EHMO calculations.
Evidence suggests tripodal rotation was also electronically hindered in the analogous fulvene complexes. Variable-temperature 13C NMR spectra of (6,6-Diphenylfulvene)Cr(CO)3 and (6-Methyl-6-phenylfulvene)Cr(CO)3 show respective 2:1 and 1:1:1 splitting of the carbonyl carbons a low temperature. Barriers of 8.3 kcal/mol and 8.8 kcal/mol were obtained by spectral simulation and were explained by using EHMO calculations.
The calculated rotational barrier for the [α-(C5H5CH2)Cr(CO)2NO]+ cation suggests that NMR spectral evidence for hindered rotation may be difficult to obtain.
Keywords: chromium, complexes, benzylic, cations, synthetic, NMR, spectroscopic, EHMO, study, temperature